GitHub training - Mishra, Abhijeet; Singh, Vartika (International Food Policy Research Institute, 2024)
The presentation was given at IFPRI's New Delhi Office Office on July 31, 2024. There is an accompanying training document detailing the steps to utilize GitHub.